E-democracy: an urgent need or a tribute to fashion? Legal analysis - Пережняк, Борис Аркадійович; Пережняк, Б. А.; Пережняк, Борис Аркадиевич; Perezhniak, Borys A.; Perezhniak, Boris; Пирога, Ігор Степанович; Пирога, І. С.; Пирога, Игорь Степанович; Pyroha, Ihor S.; Токарчук, Людмила Михайлівна; Токарчук, Л. М.; Токарчук, Людмила Михайловна; et al. (Editorial Primmate S. A. S., 2022)
The development of the information society and the strengthening of e-democracy have already become an important priority for many countries around the world at the present stage of development. The implementation of this priority implies open and transparent public administration, and thus the transformation of political institutions and processes and the introduction of new forms of government. It is meaningful to analyze the concept of “e-democracy” and to understand the importance of ensuring this in the mechanism for the democracy of each individual state. The object of research is the legal analysis of e-democracy in view of the legal realities of foreign countries. The aim of the article is a legal analysis of the concept of "electronic democracy", including problematic issues of implementation of this mechanism, in order to understand whether this mechanism is an urgent need, or is a tribute to fashion and trends in the world practice. During the study, the following methods were used: systemic, systemic-functional, comparative, sociological, analysis, synthesis, analogy, observation, classification, statistical analysis. The article analyzes the phenomenon of e-democracy, identifies the main approaches to understanding it. On the example of international experience the mechanisms of e-democracy and the peculiarities of e-government are identified. There are propositions to improve the domestic legal mechanism for e-government in the article.

Розвиток інформаційного суспільства і посилення електронної демократії вже стали важливим пріоритетом діяльності багатьох держав світу на сучасному етапі розвитку. Впровадження даного пріоритету передбачає відкрите та прозоре державне управління, а отже трансформацію політичних інститутів та процесів та запровадження новітніх форм урядування. Важливо проаналізувати поняття “електронна демократія” та зрозуміти ступінь важливості забезпечення даного в механізму для демократії кожної окремої держави. Об'єктомдослідження є правовий аналіз електронної демократії з огляду на правові реалії зарубіжних країн. Метою статті є правовий аналіз поняття “електронна демократія”, в тому числі проблемних питань реалізації даного механізму, з метою розуміння чи є даний механізм нагальною потребою, чи виступає даниною моді та тенденціям світової практики. Під час дослідження було використано такі методи як: системний, системно-функціональний, порівняльний, соціологічний, аналізу, синтезу, аналогії, спостереження, класифікації, статистичного аналізу. У статті проаналізовано феномен електронної демократії, визначено основні підходи до її розуміння. На прикладі міжнародного досвіду визначено механізми забезпечення електронної демократії та особливостей електронного урядування. У статті містяться пропозиції з удосконалення вітчизняного правового механізму забезпечення електронного урядування.
Pyroha I. E-democracy: an urgent need or a tribute to fashion? Legal analysis / I. Pyroha, L. Tokarchuk, B. Perezhniak, L. Nikitenko, V. Berch // Amazonia Investiga. – Vol. 11. – Iss. 51. – Editorial Primmate S. A. S., 2022. – P. 240-249.
Keywords: public administration; e-democracy; e-technologies; e-government; electronic court; justice; державне управління; електронна демократія; електронні технології; електронне врядування; електронний суд; правосуддя; Research Subject Categories::LAW/JURISPRUDENCE